Reconstruction of the Application of the Business Judgment Rule Principle from the Perspective of Corruption Crimes as an Effort to Overcome the Ambiguity of Norms in the Accountability of Directors - La Ode Muhamad Hiwayad; Subianta Mandala (Ridwan Institute, 2026)
The increasing complexity of corporate management has created challenges in determining the legal accountability of directors, particularly when business decisions resulting in losses are associated with corruption offenses. The application of the Business Judgment Rule principle, which is intended to protect directors who make decisions based on good faith, due care, and the best interests of the company, often encounters normative ambiguity when interacting with the corruption law regime, particularly in companies involving state finances. This study aimed to reconstruct the application of the Business Judgment Rule principle from the perspective of corruption offenses in order to establish clearer boundaries between legitimate business risks and actions that constitute criminal violations by directors. This research employed a normative juridical method using statutory and conceptual approaches. Legal materials were obtained through the examination of primary legal sources, including laws and regulations governing corporations, state-owned enterprises, and corruption eradication, as well as secondary legal sources consisting of legal literature and academic studies. The analysis was conducted qualitatively using prescriptive legal analysis. The findings indicated that normative ambiguity arose from the lack of harmonization between corporate law principles and corruption law provisions, resulting in the potential interpretation of business losses as state financial losses without adequate consideration of the decision-making process undertaken by directors. The study concluded that legal reconstruction was required by strengthening the Business Judgment Rule as an assessment standard for determining directors’ liability, establishing clearer parameters of good faith and the duty of care principle, and developing judicial guidelines to distinguish legitimate business risks from corruption-related conduct. This reconstruction was expected to provide greater legal certainty for directors while maintaining effective enforcement of corruption laws.